2020
DOI: 10.1177/2050312120940544
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of low birth weight among live birth newborns delivered at public hospitals in Gamo Gofa Zone, South Ethiopia: Unmatched case control study

Abstract: Background: Birth weight is one of the major determinants of perinatal survival, infant morbidity, and mortality. There are only few published reports on assessment of low birth weight in Ethiopia and the determinants of low birth weight have not been well characterized. Objective: The aim of this study was to assess determinants of low birth weight among live birth newborns delivered at public hospitals in Gamo Gofa Zone, South Ethiopia. Methods: Institution-based case control study was conducted from Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
11
17
0
Order By: Relevance
“…This study has identified some socio-demographic, socio-economic, obstetric and lifestyle-related factors that are associated with the delivery of LBW babies in the study area. Earlier studies from across Africa have reported some association between the delivery of LBW babies and several maternal socio-demographic, socio-economic, obstetric and medical factors [15][16][17]. In our current study, mothers who were unemployed were found to have a two-fold odds of giving birth to a LBW baby.…”
Section: Discussionsupporting
confidence: 48%
“…This study has identified some socio-demographic, socio-economic, obstetric and lifestyle-related factors that are associated with the delivery of LBW babies in the study area. Earlier studies from across Africa have reported some association between the delivery of LBW babies and several maternal socio-demographic, socio-economic, obstetric and medical factors [15][16][17]. In our current study, mothers who were unemployed were found to have a two-fold odds of giving birth to a LBW baby.…”
Section: Discussionsupporting
confidence: 48%
“…The mothers who did not receive nutrition counseling during pregnancy had higher risk to deliver low birth weight babies compared to their counterparts. This nding was consistent with other studies done in Ethiopia (9)(10)(11)the reason might be nutritional counseling improve their feeding behavior and enhance their nutritional status which may help mothers to decrease risk of delivering low birth weight babies.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies from across Africa have reported some association between the delivery of LBW babies and several maternal socio-demographic, socio-economic, obstetric and medical factors [12][13][14]. In our current study, mothers who were unemployed were found to have a two-fold odds of giving birth to a LBW baby.…”
Section: Discussionsupporting
confidence: 48%
“…This might be as a result of insu cient replacement of maternal nutrients used-up during the previous pregnancy and this may lead to reduced foetal development. A similar observation made in South Ethiopia by Mingude, et al [13] has been explained on the basis that, the short interpregnancy interval is not able to allow the mother enough time to recover from the nutritional burden and stress of the previous pregnancy, resulting in maternal nutrition depletion. The short inter-pregnancy interval is also associated with maternal iron and folic acid depletion [15].…”
Section: Discussionmentioning
confidence: 59%